Implementación De Un Sistema De Control Para Una Silla De Ruedas Mediante Señales Encefalográficas (Eeg) Y Potenciales Evocados Visuales En Estado Estacionario (Ssvep) (2023)
The present research work focuses on the predisposition to diabetes mellitus that our felines can have depending on the reproductive status that they present either whole or castrated, since they may be more likely to suffer from this disease because of various factors that may vary at the time of castration, as are weight gain and sedentary lifestyle that are given by the decrease or cancellation of some hormones related to the behavior of the animal in most cases. The objective of this study was to evaluate the levels of preprandial, postprandial glucose and glycosylated hemoglobin as tests of pancreatic functioning in neutered and whole male cats older than 3 years and less than 7 years in indora condition; This was carried out through convenience sampling where 20 cats entered the study distributed equally between neutered and whole, with an interval between samples of 20 days to complete 5 doses, and taking 1 blood sample to measure HG at the beginning and end of the study, which ran from September to March 2023 (6 months). Within the results it was observed that the average preprandial glucose in neutered felines is 83.1 and in uncastrated felines is 80.3, while the average postprandial glucose in uncastrated felines is 91.8 and in castrated felines is 89.6. Likewise, in the results of initial glycosylated hemoglobin it was observed that castrated felines presented values of 3.4, and those not castrated are at 3.2, and in the final glycosylated hemoglobin the castrated were on average 3.3 and the uncastrated in 3.2. As for the overall average prepandial glucose is 81.7, the postprandial is at 182.4 and initial glycosylated hemoglobin was 3.3 and the final 3.2. In conclusion, with this study we were able to PARÁMETROS DE LA FUNCIÓN PANCREÁTICA ENDOCRINA EN FELINOS ADULTOS… visualize not very marked variations in the results, which indicate that this predisposition may vary depending on how the other factors that can affect this condition are managed